2017
DOI: 10.1186/s12883-017-0982-3
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of chief complaints to predict severity, ventilator dependence, treatment option, and short-term outcome of patients with Guillain-Barré syndrome: a retrospective study

Abstract: BackgroundIt remains an urgent need for early recognition of disease severity, treatment option and outcome of Guillain-Barré syndrome (GBS). The chief complaint may be quickly obtained in clinic and is one of the candidates for early predictors. However, studies on the chief complaint are still lacking in GBS. The aim of the study is to describe the components of chief complaints of GBS patients, and to explore association between chief complaints and disease severity/treatment option/outcome of GBS, so as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
7
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
8
7
0
8
Order By: Relevance
“…One was autonomic dysfunction; we found that severe GBS patients with dysautonomia were more likely to need MV than those without autonomic dysfunction. This was in accordance with the results of a cohort study that reported dysautonomia as an independent predictor of respiratory insufficiency 19 , 20 and the results of Bangladesh et al that identified bulbar involvement, autonomic dysfunction, and severe muscle weakness as important risk factors for MV among Bangladeshi GBS patients 21 . Therefore, strengthening airway management is very important for GBS patients with autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…One was autonomic dysfunction; we found that severe GBS patients with dysautonomia were more likely to need MV than those without autonomic dysfunction. This was in accordance with the results of a cohort study that reported dysautonomia as an independent predictor of respiratory insufficiency 19 , 20 and the results of Bangladesh et al that identified bulbar involvement, autonomic dysfunction, and severe muscle weakness as important risk factors for MV among Bangladeshi GBS patients 21 . Therefore, strengthening airway management is very important for GBS patients with autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Islam et.al found that severe muscle weakness(MRC sum scores ranging 0 from 20) at study entry was more likely to progress to MV [21]. Autonomic dysfunction was thirteen time more common in MV patients than NV patients in the present study.It was in accordance with result of a cohort study that reported dysautonomia as an independent predictor of respiratory insu ciency [22,23]. In contract, age, facial paresis, antecedent infection, sensory, pain, place of residence and treatment option showed no association with the need for mechanical ventilation.…”
Section: Discussionsupporting
confidence: 91%
“…Pain is a relatively uncommon but still recognizable manifestation in approximately 15% of patients. 40 Around half of patients diagnosed with GBS develop autonomic dysfunction, with the most common being gastrointestinal manifestations (diarrhea/constipation) in 15% of patients, followed by hyponatremia (15%), syndrome of inappropriate antidiuretic hormone secretion (5%), bradycardia (5%), and urinary retention (4%). Other manifestations of autonomic dysfunction such as tachycardia, blood pressure instability, reversible cardiomyopathy, syncope, and Horner syndrome are rare.…”
Section: Clinical Manifestations and Variantsmentioning
confidence: 99%
“…Other manifestations of autonomic dysfunction such as tachycardia, blood pressure instability, reversible cardiomyopathy, syncope, and Horner syndrome are rare. 40,41 Cranial neuropathies can occur in up to 60% of patients and may involve multiple cranial nerves. Bulbar weakness, facial palsy, ophthalmoplegia, and hypoglossal nerve palsy are the most prevalent manifestations of cranial neuropathy.…”
Section: Clinical Manifestations and Variantsmentioning
confidence: 99%
See 1 more Smart Citation